Compliance with Professional Standards when Disclosure of Data from Sociological Surveys - Hristova, Marieta (Research Papers, 2022)
The article presents a comparative analysis of the established and applied professional standards in the publication of data from sociological research, with an emphasis on public opinion polls. This analysis is oriented in three directions: 1) description of the professional standards of some international associations, which lay the foundations for the application of ethical principles and the observance of such standards in the field of public opinion polls; 2) monitoring the discussion of the Bulgarian professional community and in particular the activity of the Bulgarian Sociological Association, related to the approval of patterns of professional standards when publishing data from pre-election surveys; 3) analysis of the Bulgarian research agencies’ publications results of pre-election surveys in the period 2014 – 2021 through a prepared monitoring tool, seeking an answer to the question: to what extent is it legal and in accordance with the professional standards the presented and published data from sociological (pre-election) research in the election campaigns periods. It is monitored whether and in what way the research agencies and centers present the passport of the research, the results of which are announced. The main monitoring indicators are derived from the Electoral Code, the codes of ethics and statements of ESOMAR, BSA, BAMOR and ABRO and include: contracting authority, contractor, financing, passport in a box, margin of error, period of conduct, sample –volume, method, representativeness, method of information registration, percentage of non-respondents, weighting, comparability, wording of the question, indicated base of the shown shares for the individual parties and place of publication.
Keywords: Professional standards; Data disclosure; Public opinion polls; Representativeness